Esperanto? Que língua é essa? - Rosa, Andrea Marques (2021)
In the linguistic environment, where the “myth of the universal language and the origin of languages” is so widespread, discussing planned languages from scientific foundation has been a challenge in Brazil. Thus, there are few scientific studies on Esperanto, created to be the international language. The absence of studies based on Discourse Analysis that deals with this language perspective and its discourse of dissemination is also noteworthy. In this sense, considering this problem, this thesis aims to analyze the discourse of Esperanto promotion, pronounced by Zamenhof ([1900] 1998), problematizing the representations of language that emerge through meaning effects. The corpus consists of seven excerpts from the translated version of the text “Esenco kaj estonteco de la ideo de lingvo internacia”, by Ludwik Lejzer Zamenhof, published in 1900. The research was guided by the hypothesis that representations of language in speech are crossed by positivist interdiscourse and by colonialist and nationalist discursive formations, which, by excluding issues of subjectivation, identity and linguistic-cultural diversity, may result in non-acceptability of an international language proposal. To achieve the goal, an analysis based on Foucault's archegenealogy was carried out, through the perspective of French Discourse Analysis. The problematizations were enabled based on theorists such as Auroux (1998; 2008), Gadet and Pêcheux (2010) and Milner (2012) for reflections on “universal language”; Authier-Revuz (1990; 1998), on heterogeneities in discourse; Foucault (2009; 2010; 2014; 2016; 2017a; 2017b ), to support the analysis, based on archeology, power/knowledge relations, resistance and subject; CORACINI (1991), to deal with political discourse and scientific discourse; and others. The thesis is divided into three chapters. The first chapter presents the production conditions of Zamenhof's discourse; in the second one, the theoretical-methodological aspects that guide the research are described ; and, the third chapter is focuses on the analysis. Through meaning effects, the analysis demonstrates the following representations of the language emerged from Zamenhof's discourse, which are also representations of Esperanto as an international language: a) as a public space that allows political practice, through friendship policy; b) as a “language-nation”, an “imaginary territory”; c) as a real non-located space for advocating accounts, a “glossotopia”; and, d) as a “translingua per se”. The hypothesis confirmation reveals that power/knowledge relations are a considerable obstacle to the adoption of Esperanto as an international language, especially when the discourse of promotion prioritizes the positivist interdiscourse, marginalizing the problematization of identity issues.